MENGANALISIS STRATEGI PENGEMBANGAN PROFESIONALISME GURU DALAM PEMBELAJARAN SEUMUR HIDUP DI ERA DIGITAL: TANTANGAN DAN PELUANG - Ginting, Anisa Nur Baidah; Zahra, Salwa; Aulia, Mita; Zahra, Latifah; Sigiro, Martina; Purba, Sasta Glovia Talenta; Nainggolan, Elizon; Subaedah, Sitti (Jurnal Manajemen Pendidikan, 2025)
This study examines the integration of digital technology in learning and the professional development of teachers in the digital era at the elementary school level. The digital transformation requires teachers to master digital competencies in order to deliver interactive and innovative instruction. The study is motivated by various challenges, including limited formal training, inadequate digital infrastructure, and the differing instructional needs between lower and upper elementary levels. A review of literature supports that enhancing digital literacy through TPACK models and intensive training approaches is an effective strategy to improve teaching quality. Data were collected through in-depth interviews with two teachers (from a first-grade class and a fifth-grade class) and current literature studies. Content and thematic analysis were employed to identify key issues regarding technological integration and professional development strategies. The results reveal that limited formal training and digital infrastructure adversely affect the teaching process, while participation in workshops and peer collaboration enhances teachers’ digital competencies. These findings provide strategic recommendations for schools and education authorities to develop continuous training programs tailored to the specific needs of each educational level.